Estimation of apparent tumor vascular permeability from multiphoton fluorescence microscopic images of P22 rat sarcomas in vivo. - Reyes-Aldasoro, C; Wilson, I; Prise, V; Barber, P; Ameer-Beg, M; Vojnovic, B; Cunningham, V; Tozer, G (2008)
OBJECTIVE: To develop an image processing-based method to quantify the rate of extravasation of fluorescent contrast agents from tumor microvessels, and to investigate the effect of the tumor vascular disrupting agent combretastatin A-4-P (CA-4-P) on apparent tumor vascular permeability to 40 kDa fluorescein isothiocyanate (FITC) labeled dextran. METHODS: Extravasation of FITC-dextran was imaged in 3 dimensions over time within P22 sarcomas growing in dorsal skin flap "window chambers" in BDIX rats using multiphoton fluorescence microscopy. Image processing techniques were used to segment the data into intra- and extravascular regions or classes. Quantitative estimates of the tissue influx (vascular leakage) rate constant, K(i), were obtained from the time courses of the fluorescence intensities in the two classes. Apparent permeability, P, was calculated, assuming K(i) = PS/V, where S is vascular surface area in tumor volume V. RESULTS: Combining image processing and kinetic analysis algorithms with multiphoton fluorescence microscopy enabled quantification of the rate of tumor vascular leakage, averaged over a large number of vessels. Treatment with CA-4-P caused a significant increase in K(i) from 1.13 +/- 0.33 to 2.59 +/- 0.20 (s(- 1)x 10(- 4); mean +/- SEM), equivalent to an increase in P from 12.76 +/- 3.36 to 30.94 +/- 2.64 (cm s(-1)x 10(-7)). CONCLUSIONS: A methodology was developed that provided evidence for a CA-4-P-induced increase in tumor macromolecular vascular permeability, likely to be central to its anti-cancer activity.